Mechanistic insights into Smiles rearrangement. Focus on π–π stacking interactions along the radical cascade. Issue 35 (26th August 2020) - Khartabil, Hassan; Doudet, Ludovic; Allart-Simon, Ingrid; Ponce-Vargas, Miguel; Gérard, Stéphane; Hénon, Eric
Abstract : The synthesis of new arene and heteroarene scaffolds of therapeutic interest has generated a renewed interest in the domino radical cyclisation–Smiles. Abstract : The synthesis of new arene and heteroarene scaffolds of therapeutic interest has generated a renewed interest in the domino radical cyclisation–Smiles. In this work we present a detailed mechanistic investigation of the radical version of a cascade involving a desulfonative Smiles rearrangement on an aromatic ring bearing a sulfonamide linker. Competing routes have been explored to characterize the molecular mechanism of the studied reaction. The knowledge gained from previous experimental observations is explained through the energy profile obtained by means of quantum mechanical calculations. This study answers questions about the rate determining step and the type of mechanism involved (two-step or concerted). Supplementary rate constant calculations as well as quantum molecular dynamics support experimental observations. An IGM-δ g analysis performed along the reaction path unveils and quantifies an intramolecular π–π stacking interaction accelerating the reaction. This novel post processing IGM-δ g tool based on the electron density, turns out to be useful to monitor and quantify specific intramolecular weak interactions along a reaction path from wave functions. From this mechanistic investigation it turns out that Smiles rearrangement here takes place in two steps rather than in a direct intramolecular radical substitution. Furthermore, we show that chain length effects must be taken into account in the functionalization of new sulfonylated derivatives subjected to this radical cascade, given their influence in the reaction rate.